Microvessel density assessment in canine mammary carcinomas as a predictive factor for metronomic chemotherapy - Ferrari, Analy Ramos Mendes [UNESP]; Ferrari, Heitor Flavio; Carreira, Vinicius Soares; Frigério, Edenilson Doná [UNESP]; Luvizotto, Maria Cecília Rui [UNESP]; De Andrade, Alexandre Lima [UNESP] (Universidade Estadual de Londrina, 2019)
The canine mammary tumor is the neoplasia that most commonly affects intact female dogs (not spayed) in routine veterinary practice. Canine mammary tumor therapy is a challenge because only few effective treatments have been described for high-grade tumors in veterinary medicine. One such therapeutic option that slows down tumor growth is metronomic chemotherapy (MC), a therapeutic modality that acts by decreasing tumor angiogenesis. Quantification of intratumoral microvessel density (MVD) has been proposed as a means to evaluate the effectiveness of MC in human and canine tumors. In this study, MVD is proposed as a predictive factor for the effectiveness of MC in canine mammary tumors. Twenty female dogs with mammary carcinoma were equally distributed into a mastectomy group treated only with mastectomy, and a MC group treated with MC (cyclophosphamide and piroxicam) orally and daily for 28 days followed by mastectomy. Mammary tumors were classified and graded histologically. MVD was ascertained by CD31 immunostaining. The analysis showed statistically significant difference in MVD scores between groups, corroborating a quantitative reduction in tumor microvasculature in the group treated with MC. Our findings suggest that MVD may be an important predictive factor for the selection of female dogs with malignant mammary tumors that may benefit from MC.
Keywords: Angiogenesis; Antiangiogenic chemotherapy; Female dog; Mammary tumor